Evaluation of pharmacokinetics of warfarin from validated pharmacokinetic-pharmacodynamic model - Kannan Sridharan; Rashed Al Banna; Aysha Husain (International Association of Physical Chemists (IAPC), 2021)
Background: Pharmacokinetics of warfarin has not been described in our population. We derived the pharmacokinetic parameters from a validated pharmacokinetic-pharmacodynamic model. Methods: Patients receiving warfarin for at least 6 months were recruited and their demographic characteristics, prothrombin time international normalized ratio (PT-INR), warfarin doses and concomitant drugs were collected. Using a validated pharmacokinetic-pharmacodynamic model, we predicted maximum plasma concentration (Cmax), total clearance (CL), volume of distribution (Vd) and elimination rate (k). Warfarin sensitive index (WSI) and warfarin composite measures (WCM) were estimated from the dose and INR values. Liver weight was predicted using validated formula. Results: Two-hundred and twenty patients were recruited. The following were the predicted pharmacokinetic parameters: Cmax (mg/L) was 5.8 (0.4); k (L/day) was 1 (0.1); CL (L/day) was 2.1 (0.2); and Vd (L) was 7.6 (0.2). Patients with Cmax and elimination rate outside the mean+1.96 SD had significantly lower WSI and higher WCM. Significant correlations were observed between Cmax with CL, Vd, and k of warfarin. Significant correlations were also observed between CL and Vd of warfarin with liver weight of the study participants. Conclusion: We predicted pharmacokinetic parameters of warfarin from the validated pharmacokinetic-pharmacodynamic model in our population. More studies are needed exploring the relationship between various pharmacodynamic indices of warfarin and pharmacokinetic parameters of warfarin.